2009
DOI: 10.1016/j.bpj.2008.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Size, Structure, and Stability of Tight Protein Knots

Abstract: Approximately 1% of known protein structures display knotted configurations in their native fold, but the function of these configurations is not understood. It has been speculated that the entanglement may inhibit mechanical protein unfolding or transport, e.g., as in cellular threading or translocation processes through narrow biological pores. Protein knot manipulation, e.g., knot tightening and localization, has become possible in single-molecule experiments. Here, we investigate tight peptide knot (TPK) c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 54 publications
5
43
0
Order By: Relevance
“…Pulling in the 2/209 direction provides a size estimate for the 3 1 knot of 5.7 nm, which corresponds to ∼16 amino acid residues. This value is in good agreement with atomic force microscopy (AFM) measurements on AFV3-109 (47) and phytochrome C (48), as well as values from simulations of tight knots in polypeptide chains under force (49).…”
Section: Discussionsupporting
confidence: 77%
“…Pulling in the 2/209 direction provides a size estimate for the 3 1 knot of 5.7 nm, which corresponds to ∼16 amino acid residues. This value is in good agreement with atomic force microscopy (AFM) measurements on AFV3-109 (47) and phytochrome C (48), as well as values from simulations of tight knots in polypeptide chains under force (49).…”
Section: Discussionsupporting
confidence: 77%
“…In these proteins, the disadvantage of less efficient folding may be balanced by a functional advantage connected with the presence of these knots. Numerous experimental (13)(14)(15)(16) and theoretical (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) studies have been devoted to understanding the precise nature of the structural and functional advantages created by the presence of these knots in protein backbones. It has been proposed that in some cases the protein knots and slipknots provide a stabilizing function that can act by holding together certain protein domains (4).…”
mentioning
confidence: 99%
“…Trefoil, figure-of-eight, and penta knots with three, four, and five projected crossings of the polypeptide backbone, respectively, have been observed in proteins from all three domains of life (11)(12)(13). The functional advantages of knotted structures over their unknotted counterparts are unknown, although various computational studies have suggested that topological knots may increase protein stability or resistance to cellular translocation and degradation pathways (11,(14)(15)(16). Whereas various routes for protein knotting have been proposed, examples of which include the existence of an intermediate "slipknot" configuration or specific, attractive nonnative contacts that promote a threading event (17)(18)(19), these models have yet to be experimentally verified.…”
mentioning
confidence: 99%